First-line Immune Checkpoint Inhibitor Versus Immune Checkpoint Inhibitor With Chemotherapy for Cisplatin-ineligible Metastatic Urothelial Carcinoma: Evidence From a Real-world, Multicenter Analysis. Issue 9 (20th November 2022) - Lin, Chang-Ting; Su, Po-Jung; Huang, Shih-Yu; Wu, Chia-Che; Wang, Hung-Jen; Cheng, Yuan-Tso; Luo, Hao-Lun; Chen, Chien-Hsu; Liu, Ting-Ting; Huang, Chun-Chieh; Su, Yu-Li
Abstract : Immune checkpoint inhibitors (ICIs) are widely used for first-line cisplatin-ineligible patients with metastatic urothelial carcinoma (mUC). However, whether to use ICIs as monotherapy or in combination with chemotherapy is still uncertain. We retrospectively analyzed cisplatin-ineligible patients with mUC who underwent first-line ICI monotherapy or ICI plus chemotherapy at 2 medical centers in Taiwan from 2016 to 2021. We calculated the objective response rate, progression-free survival, and overall survival (OS) using the Kaplan-Meier method and Cox regression model for multivariable analysis. In total, 130 patients were enrolled and categorized into 2 groups: an ICI monotherapy group [immunotherapy (IO), n=101] and an ICI plus noncisplatin chemotherapy group [immunotherapy and chemotherapy (IC), n=29]. The median OS of patients in the IO and IC groups was 19.5 and 9.7 months ( P =0.33). Among patients with high programmed cell death ligand-1–expressing tumors, the median OS was significantly prolonged in the IO group compared with the IC group (not reached vs. 6.3 mo, P =0.02). First-line ICI monotherapy demonstrated robust antitumor activity in cisplatin-ineligible patients with mUC. Combining noncisplatin chemotherapy with ICI did not improve clinical outcomes.